Experience of reversal of sterilisation at Glasgow Royal Infirmary. Issue 1 (1st January 2003) - Prabha, Sivaraman; Lunan, C Burnett; Hill, Robert
Abstract : Objective: To review experience at the Glasgow Royal Infirmary with regard to women who underwent reversal of sterilisation, to obtain a profile of these women and to evaluate the procedure itself in terms of safety and restoration of fertility. Design: A retrospective study based on case records from the Glasgow Royal Infirmary and from the Glasgow Royal Maternity Hospital, both of which share the same catchment area. Participants: Eighty-five women underwent reversal of sterilisation between 1 January 1994 and 31 December 1998 at the Glasgow Royal Infirmary. Follow-up at the Glasgow Royal Maternity identified 43/85 women. Methods: Patients were identified from relevant theatre log books and from records at the maternity hospital until December 2000 and their case notes reviewed. Results: Having a new partner was responsible for 90% of requests. Median age at request for reversal was 34 years and most had been sterilised before the age of 30 years. There were few postoperative complications. Pregnancy occurred in at least 43% of women. Conclusion: Reversal of sterilisation is a safe and effective method of restoring fertility. The actual incidence of pregnancy after reversal is likely to be higher than the 43.5% recorded due to difficulties in achieving 100% follow-up.